Pengembangan Media Powerpoint Interaktif Konstruktivisme untuk Meningkatkan Pemahaman Konsep Luas Bangun Datar Siswa Sekolah Dasar - Budiawan, Wahrul; Muslim, Rachmat Imam; Wuryani, Meilan Tri (Jurnal Gentala Pendidikan Dasar, 2026)
Mathematics learning on plane geometry area in elementary schools still faces challenges related to students’ low conceptual understanding, as instruction often emphasizes procedural use of formulas. This condition raises the question of how learning media can be developed to support students in constructing a better understanding of plane geometry area concepts. This study aims to develop and analyze the effectiveness of constructivism-based interactive PowerPoint learning media in improving elementary school students’ understanding of plane geometry area. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The learning media were implemented with 17 randomly selected fifth-grade elementary school students. Data were collected through pretest and posttest and analyzed using the normalized gain (N-Gain). The results indicate an improvement in students’ conceptual understanding, with the average pretest score increasing from 50.12 to 69.18 in the posttest. The obtained N-Gain value of 0.38 falls into the moderate category. These findings suggest that constructivism-based interactive PowerPoint media can be used as an alternative learning medium to support students’ understanding of plane geometry area concepts more effectively.